A Genetic Screen Identifies PRP18a, a Putative Second Step Splicing Factor Important for Alternative Splicing and a Normal Phenotype in Arabidopsis thaliana. Issue 4 (1st April 2018) - Kanno, Tatsuo; Lin, Wen-Dar; Chang, Chia-Liang; Matzke, Marjori; Matzke, Antonius J M
Abstract: Splicing of pre-mRNA involves two consecutive trans -esterification steps that take place in the spliceosome, a large dynamic ribonucleoprotein complex situated in the nucleus. In addition to core spliceosomal proteins, each catalytic step requires step-specific factors. Although the Arabidopsis thaliana genome encodes around 430 predicted splicing factors, functional information about these proteins is limited. In a forward genetic screen based on an alternatively-spliced GFP reporter gene in Arabidopsis thaliana, we identified a mutant impaired in putative step II factor PRP18a, which has not yet been investigated for its role in pre-mRNA splicing in plants. Step II entails cleavage at the 3′ splice site accompanied by ligation of the 5′ and 3′ exons and intron removal. In the prp18 mutant, splicing of a U2-type intron with non-canonical AT-AC splice sites in GFP pre-mRNA is reduced while splicing of a canonical GT-AG intron is enhanced, resulting in decreased levels of translatable GFP mRNA and GFP protein. These findings suggest that wild-type PRP18a may in some cases promote splicing at weak, non-canonical splice sites. Analysis of genome-wide changes in alternative splicing in the prp18a mutant identified numerous cases of intron retention and a preponderance of altered 3′ splice sites, suggesting an influence of PRP18a on 3′ splice site selection. The prp18a mutant featured short roots on synthetic medium and small siliques, illustrating that wild-type PRP18a function is needed for a normal phenotype. Our study expands knowledge of plant splicing factors and provides foundational information and resources for further functional studies of PRP18 proteins in plants.